2020
DOI: 10.22159/ijcpr.2020v12i2.37491
|View full text |Cite
|
Sign up to set email alerts
|

Visible Spectrophotometric Method Development and Validation of Imatinib in Bulk and Formulation

Abstract: Objective: A new, simple, sensitive, precise and reproducible UV visible spectrophotometric method was developed for the determination of Imatinib in pharmaceutical formulations with alizarin. Methods: The method is based on formation of yellow-colored complex. The UV spectrum of Imatinib in methanol showed λ max at 431 nm. Beer’s law is valid in the concentration range of 10-70 μg/ml. This method was validated for linearity, accuracy, precision, ruggedness and robustness. Results: The method has d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Reviewing the mobile phase systems used in the previously published TLC-densitometric methods which were developed for the determination of either HCZ with other drugs [ 34 40 ], HCZ with its impurities [ 41 43 ], or CPL in combination with other drugs [ 44 46 ], it was found that, in most manuscripts, methanol was used in combination with either ethyl acetate or chloroform. Chloroform was excluded for its toxic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Reviewing the mobile phase systems used in the previously published TLC-densitometric methods which were developed for the determination of either HCZ with other drugs [ 34 40 ], HCZ with its impurities [ 41 43 ], or CPL in combination with other drugs [ 44 46 ], it was found that, in most manuscripts, methanol was used in combination with either ethyl acetate or chloroform. Chloroform was excluded for its toxic effect.…”
Section: Resultsmentioning
confidence: 99%